Contested Borderland : The Civil War in Appalachian Kentucky and Virginia - McKnight, Brian Dallas (Book collections on Project MUSE., 2006)
From 1861 to 1865, the border separating eastern Kentucky and south-western Virginia represented a major ideological split. This book shows how military invasion of this region led to increasing guerrilla warfare, and how regular armies and state militias ripped communities along partisan lines, leaving wounds long after the end of the Civil War.